Cancer-derived exosomal miR-197-3p confers angiogenesis via targeting TIMP2/3 in lung adenocarcinoma metastasis - Rui-Min Chang; Yao Fu; Jun Zeng; Xiao-Yan Zhu; Yang Gao (Cell Death and Disease, 2022)
Abstract Cancer-derived exosomal miRNAs are implicated in tumorigenesis and development of lung adenocarcinoma (LUAD). The objective of this study is to unravel the biological function of exosomal miR-197-3p in LUAD metastasis. qRT-PCR showed that elevated miR-197-3p in LUAD tissues was positively correlated with LUAD metastasis. CCK-8, tube formation, transwell and wound healing assays revealed that exosomal miR-197-3p from LUAD cells promoted the proliferation, angiogenesis and migration of HUVECs in vitro. LUAD cells-derived exosomal miR-197-3p also facilitated tumor growth and angiogenesis in LUAD cells-derived tumor xenograft model. TIMP2 and TIMP3 were identified as target genes of miR-197-3p in HUVECs by bioinformatics analysis and luciferase reporter assay. Functional studies illustrated that exosomal miR-197-3p promoted angiogenesis and migration via targeting TIMP2 and TIMP3 in HUVECs. In vivo data further supported that exosomal miR-197-3p promoted lung metastasis via TIMP2/3-mediated angiogenesis. In conclusion, LUAD cells-derived exosomal miR-197-3p conferred angiogenesis via targeting TIMP2/3 in LUAD metastasis.